Ambulant food vending (pungko-pungko) in the vicinity of secondary schools Cebu city experience - Gantuangko, Neri R. (Danyag : Journal of Humanities and Social Sciences, 2007)
This study attempts to present a general demographic profile of 36 other ambulant vendors plying between some Cebu City secondary schools vis-a-vis attitudes toward issues affecting food vending. It also solicits information from the 'demand side' - 124 student-clients from both public and private schools, the supply side (source of vendor's supply) and from other stake holders. The triangulation research methodology was used, including use of survey questionnaires, guided interviews and documentary and secondary data reviews. The findings show a group of vendors who are largely male, married, high school level, young (26-30 yrs.old), and who have been with this activity between 5-9 years, and getting seemingly sufficient income. Majority (24) get their food supply on 'angkat' (trust), which are paid at the end of the day. The rest cook their own food. All vendors have an indigenous business style and food handling techniques. Price and taste are prime considerations for the students' choice of street food, despite awareness of the possibility of unsanitary food handling. Long-term consequences of poor diet and unsanitary food handling seem not to be considered seriously. Documents suggest that the local government units have an ambivalent attitude towards ambulant vendors, who, on the other hand, would rather be left alone.